GAMBARAN KETAATAN MASYARAKAT USIA REMAJA TENTANG KEBIJAKAN PEMERINTAH MENGENAI PENANGANAN COVID-19 DI WILAYAH KECAMATAN CIMERAK KABUPATEN PANGANDARAN - Nova Merlianda; Jajuk Kusumawaty; Ayu Endang Purwati; Irpan Ali Rahman Irpan (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2022)
COVID-19 is a new type of infectious disease that attacks the respiratory tract with an increasing number of cases including adolescents. The Indonesian government has made efforts to deal with a form of national resilience in breaking the chain of transmission of COVID-19 in the community, including policies such as wearing masks, maintaining distance and washing hands. Objective of this study was to find out the adherence of the adolescent community regarding government policies regarding the handling of COVID-19 in the Cimerak District, Pangandaran Regency. The method used in this research is descriptive quantitative. This sampling technique used purposive sampling to the adolescent community as many as 97 respondents in the Cimerak District. This research was conducted in March 2021. Results of this study found that obedience of the adolescent community regarding the handling of COVID-19 found that most of the respondents had obeyed as many as 53 respondents (54.6%), while as many as 44 (45.4%) respondents were disobedient. Conclusion of this study states that the 97 respondents who became respondents had good compliance in handling COVID-19.